GOVERNMENT POLICY OF THE CITY OF BANJARMASIN ON REDUCING THE USE OF PLASTIC BAGS (A CASE STUDY OF A GOVERNMENT POLICY OF THE CITY OF BANJARMASIN) - M. Sayuti Enggok; Normajatun; Deli Anhar (Bajang Institute, 2022)
This study aims to determine the implementation of Banjarmasin city government policies in reducing the use of plastic bags in traditional markets in the city of Banjarmasin. This study uses a qualitative approach with a descriptive analysis method. As a key informant, the Head of the Sanitation and Waste Management Office of the Banjarmasin City Environmental Service has been interviewed to collect data. To complete the data, we also interviewed both sellers and buyers in the markets of Pandu and TelukDalam Banjarmasin City. The results showed that the city government had implemented the policy through a socialization program in communication and transmission. The socialization program has been implemented in almost all the markets owned by the Banjarmasin city of government. Through the socialization program, we were found that the implementation of the policy was clear and consistent. The Banjarmasin City Environmental Service apparatus is the human resource involved in implementing the policy. The other resources came from the Banjarmasin City Regional Revenue and Expenditure Budget in budget sources. In terms of disposition, policy implementers are committed to carrying out their duties properly and democratically. The existence of Standard Operating Procedures has guided the policy implementation in terms of bureaucratic structure. However, implementation constraints still exist, such as public response, including the general understanding of the policy's benefits to reduce the use of plastic bags.